Answer:
a. (3-7x) + (3-7x) + (3-7x) + (3-7x)
b. 4(3-7x)
c. 12 - 28x
Explanation:
To find the perimeter of a square, you need to add up all the sides
a. Since a square has all equal sides you will need to write the expression four times: (3-7x) + (3-7x) + (3-7x) + (3-7x) = perimeter
b. Expressing this as a product, we can condense the formula to 4 multiplied by the expression since it is written four times: 4(3-7x) = perimeter
c. Using the distributive property, we can write the product 4(3-7x) from b. as: (4)(3) + (4)(-7x) = 12 + (-28x) = 12 - 28x = perimeter